2021
DOI: 10.1021/acssuschemeng.0c09073
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Recovery from Lead-Rich Dross of Lead Smelter and Conversion into Antimony Oxide Chloride (Sb4O5Cl2)

Abstract: Antimony was selectively leached from a lead-rich industrial process residue called 'dross', and recovered as an antimony oxide chloride (Sb4O5Cl2), which can be used as a component in flame retardants or as an anode material in aqueous chloride batteries. The dross is a residue generated by a lead smelter and it contained about 30 wt% of lead and about the same concentration of antimony, along with some minor metals such as zinc, iron and tin. Solutions of hydrochloric acid dissolved in organic solvents such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…We assume a hydrolysis of the [AlCl 4 ] – anions, in which acidic [Al(H 2 O) 6 ] 3+ (p K a =4.97) is formed on the surface of the initial crystals (Equation 2). Sb 4 O 5 Cl 2 (besides SbOCl) is a known product of the hydrolysis of SbCl 3 in acidic aqueous solutions [51–53] . Here, Sb 4 O 5 Cl 2 could have formed via an intermediate compound “Cu(Sb 2 S 3 )Cl” (see below) by a solution process in which the antimony and part of the sulfide ions are removed from the crystal (Equation 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume a hydrolysis of the [AlCl 4 ] – anions, in which acidic [Al(H 2 O) 6 ] 3+ (p K a =4.97) is formed on the surface of the initial crystals (Equation 2). Sb 4 O 5 Cl 2 (besides SbOCl) is a known product of the hydrolysis of SbCl 3 in acidic aqueous solutions [51–53] . Here, Sb 4 O 5 Cl 2 could have formed via an intermediate compound “Cu(Sb 2 S 3 )Cl” (see below) by a solution process in which the antimony and part of the sulfide ions are removed from the crystal (Equation 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sb 4 O 5 Cl 2 (besides SbOCl) is a known product of the hydrolysis of SbCl 3 in acidic aqueous solutions. [51][52][53] Here, Sb 4 O 5 Cl 2 could have formed via an intermediate compound "Cu(Sb 2 S 3 )Cl" (see below) by a solution process in which the antimony and part of the sulfide ions are removed from the crystal (Equation 3). The aluminum-containing hydrolysis product did not solidify and was therefore not detected in the EDX or the diffractogram.…”
Section: Reactivitymentioning
confidence: 99%
“…Then, the generated Sb 4 Cl 2 O 5 was further converted into Sb 2 O 3 with an excellent crystal form and high purity by using Na 2 CO 3 , NaOH, or NH 4 OH as mediating agents. Palden et al [22] compared the effects of potassium carbonate, sodium sulfide, and water on the precipitation of antimony from lead dross, and found that Sb(III) in solution can undergo hydrolysis in water to generate Sb 4 Cl 2 O 5 . These investigations presented the potential for utilizing the granulation process in antimony recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the presence of Sb 2 O 3 became apparent within a pH range of approximately 8 to 9. Accordingly, researchers in [23] generate Sb 4 O 5 Cl 2 by adding water into an ethanol-based HCl solution with a concentration of 2 mol/L. Total precipitation is determined to occur in a volumetric ratio of 1 between the added water and original solution.…”
Section: Introductionmentioning
confidence: 99%